Perancangan Sistem Informasi Penggajian Pegawai di Kantor Camat Pangga Kabupaten Aceh Jaya - Sabaruddin; Fathurrahmad; Abdussalam (Design Journal, 2023)
The development of a web-based employee payroll information system has become an important solution in increasing the effectiveness and efficiency of the payroll process in various agencies, including the Panga Aceh Jaya Subdistrict Office. This research aims to design and implement a website-based employee payroll information system to improve the manual payroll process in the office. The development method used is the SDLC method with a waterfall approach. The result is a web application that allows users to manage employee data and payroll processes efficiently. This application has features such as a login form, employee data input, recapitulation, and payroll reports. The conclusion of this research shows that the implementation of this system has brought significant benefits in increasing the accuracy and speed of the payroll process. However, to increase the effectiveness of the system, it is recommended to optimize the use of computers and improve training for the workforce in interacting with the system. By implementing these suggestions, it is hoped that the performance of the information system can be further improved to provide greater benefits for the Panga Aceh Jaya Subdistrict Office.